2017
DOI: 10.4018/ijtem.2017010101
|View full text |Cite
|
Sign up to set email alerts
|

International Students' Perceptions of Services and Supports Provided

Abstract: In a study of international students' perceptions of services and supports offered by the mid-sized institution in which they are currently enrolled, consisting of 103 international students onshore in the USA, it was found that the majority of the respondents were fully aware of the International Student Orientation (ISO) that is made available to them via the Office of International Education (OIE). However, only close to 70% of the respondents had attended the orientation, even though the university claimed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…A descriptive research design was suitable for this study as it frequently uses data collection methods such as questionnaire survey that involves "asking respondents structure questions about what they think, feel and do" (Hair, Celsi, Ortinau & Bush, 2017, p. 109). Some benefits of using an online survey are to make sure that the responses were gathered in a standardized way (Ho, 2017) and large amounts of information can be collected from a large number of respondents in a short period of time and a relatively cost-effective way (Hair, et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…A descriptive research design was suitable for this study as it frequently uses data collection methods such as questionnaire survey that involves "asking respondents structure questions about what they think, feel and do" (Hair, Celsi, Ortinau & Bush, 2017, p. 109). Some benefits of using an online survey are to make sure that the responses were gathered in a standardized way (Ho, 2017) and large amounts of information can be collected from a large number of respondents in a short period of time and a relatively cost-effective way (Hair, et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…In recognition of these challenges, many universities provide orientation sessions for international students and other pre-academic programming. In the United States, research on this topic is often found among publications related to support for international students-especially students from China-focusing on international student orientation (Rose-Redwood & Rose-Redwood, 2013), international student services (Ho, 2017), or in ways for faculty to engage international students throughout their degrees (Heng, 2017). However, there are few empirical studies on private philanthropic organizations who provide academic preparation in the form of a foundation-led summer academic program, especially for individuals who are going to receive a master's degree abroad.…”
Section: Introductionmentioning
confidence: 99%
“…International partnerships make it possible for the HEIs to improve on the quality of their academic and research programmes and internationalise their curriculum, thereby increasing patronage and improving their status in the academic and industrial environment, locally and internationally (Ho, 2017;Warwick, 2014). HEIs are motivated by access to knowledge for research, since localised knowledge is not enough to make the conclusions that research findings are applicable internationally (Costa, Soares, & de Sousa, 2016).…”
Section: Academic Motivesmentioning
confidence: 99%